Concept of Management Higher Islamic Education at Mohammad Natsir Institute of Da'wah - Patahuddin, Askar; Hafidhuddin, Didin; Indra, Hasbi; Handrianto, Budi; Assiroji, Dwi Budiman (PT. Riset Press International, 2024)
Quality Islamic education is education that produces graduates who have skills not only in one discipline, because the purpose of Islamic Education according to M. Natsir is to produce preachers who are sincere, have militancy and are competent. Various kinds of problems in the community, nationality and social dynamics of Indonesian society require graduates of Islamic universities to have diverse skills, including aspects of knowledge, faith, worship supported by noble morals. This research aims to reveal the concept of management of Islamic higher education at the M. Natsir College of Da'wah. The research method used is descriptive qualitative on the object of the literature studied, then using a case study to compile the concept of education management of STID Mohammad Natsir. The findings obtained, that the management of Islamic higher education at STID M. Natsir aims to produce preachers in all study programmes. Student input is done by selecting students from various regions and delegates of the Indonesian Islamic da'wah council from the competence of reading the Qur'an, basic understanding of Islam and orientation to become a preacher after graduation. The higher education process combines three components, namely mosque, Pesantren and campus, and the educational output is ready to become preachers in remote and inland areas. This concept was inspired by the educational ideas of Mr M. Natsir.